STUDI TEKNOLOGI PERENGKAHAN PANAS DAN PENJENUHAN TRIGLISERIDA CRUDE PALM OIL PADA KONDISI BASA DENGAN TWO STAGES ELECTROCHEMICAL THERMAL CRACKING REACTOR - Trisnaliani, Lety; Purnamasari, Indah (KINETIKA, 2014)
The study was experienced using electrolyze by using two stages electrochemical thermal cracking reactor, zeolyte  as catalyst, silver as cathode and cuprum as anode. In this research, we used electrolyte solution for 2 kinds of pH  which  was  pH  10  and  pH  12  of  Potassium  Hydroxide  (KOH)  and  different  voltage  which  was  2,4,6,8,10  and  12  volt.  It  worked  in  1  atmosphere  with  electrolyze  for  1  hour,  heating  till  reaching  temperature  80 oC  for  1  hour, fogging process for 1 hour, and heating without electrolyze nor fogging about 30 minutes. From lubricity analyze,  this product is a fuel with high lubricity. The analyzer showing that cracking of triglyceride of crude palm oil has  same characteristics with diesel.